POST-COVID-19 TOURISM SECTOR POLICY RECOMMENDATIONS FOR SHORT, MEDIUM, AND LONG-TERM PLANNING - Pambudi, Andi Setyo (Jurnal Politik Pemerintahan Dharma Praja, 2023)
Tourism is one of the sectors most affected by the COVID-19 pandemic. This pandemic has prompted governments worldwide to implement policies to limit community activities, both within and between countries. The tourism sector has been significantly affected, especially regarding income reduction, due to the cessation of supporting factors such as providing accommodation and food and beverages; retail and wholesale trade; car and motorcycle repairs; and transportation and warehousing. Before the emergence of the COVID-19 pandemic, the focus of 5-year tourism development in Indonesia was on strengthening priority tourism destinations and revitalizing Bali destinations. The COVID-19 pandemic that began in March 2020 has changed the 5-year tourism sector projection, followed by various policies to prevent the spread of this virus and focus on public health. This study aims to present a portrait of Indonesian tourism at the beginning of the COVID-19 pandemic and provide recommendations for recovering economic policy adaptations, both short-term and medium- and long-term. The method used is a literature review with a qualitative and descriptive approach to existing policies. The results of the analysis recommend that the assessment of tourism development planning be emphasized on general stimulus, stimulus for Small, micro, and Medium Enterprises (MSMEs), structuring accommodation packages, transportation and access, taxation stimulus, technical guidance, strengthening tourism diversification, and strengthening the supply and demand side of the tourism sector.